Tinjauan Yuridis Diskresi pada Birokrasi Digital - Intan Lovisonnya; Astrid Amidiaputri Hasyyati (Lembaga Pengembangan Kinerja Dosen, 2024)
Digital bureaucracy is a new bureaucratic system that arises because of globalization, as well as a substitute for the classic bureaucratic concept, namely paper-based bureaucracy. Digital bureaucracy has a role in improving the good governance system, by increasing the four indicators of good governance principles, namely transparency, accountability, efficiency and effectiveness. Indonesia can take advantage of the existing demographic bonus. Human resource management as the foundation for running the digital governance wheel is an important key. Adoption of technology in various public service sectors and supported by human resources with high digital adaptability is expected to increase the competitiveness of our governance. The state has a goal in realizing the welfare of its people. So that the state needs to do various things in meeting the needs of the community through the implementation of public services. In order to meet the needs of the community to run well, the urgency related to the quality of public services is very large. As for what affects the quality of public services, one of them is internal factors, namely discretionary authority,actions determined, carried out by government officials to overcome concrete problems faced in the administration of government in terms of laws and regulations that provide choices, do not regulate, are incomplete or unclear,there is government stagnation. Discretion is used by the government for and on behalf of positions, carried out within the formal environment of the authority of government officials, its implementation is directed at effectiveness and efficiency, and must be in accordance with AUPB, and based on the principle of rationality. Any use of government officials' discretion is aimed at facilitating government administration, filling legal voids.